Increased Lyso-Gb1 Levels in an Obese Splenectomized Gaucher Disease Type 1 Patient Treated with Eliglustat: Unacknowledged Poor Compliance or Underlying Factors - Evelina Maines; Roberto Franceschi; Giacomo Luppi; Giacomo Marchi; Giovanni Piccoli; Nicola Vitturi; Massimo Soffiati; Annalisa Campomori; Silvana Anna Maria Urru (Metabolites)
Eliglustat (Cerdelga®) is a potent and specific inhibitor of the enzyme glucosylceramide synthase and serves as a substrate reduction therapy for adult patients with Gaucher disease type 1 (GD1). It prevents the accumulation of several lipids, including glucosylsphingosine (also known as Lyso-Gb1). In addition to its role in diagnostics, Lyso-Gb1 has been proven to be a reliable biomarker for assessing disease severity and monitoring treatment efficacy. We present the case of an obese, splenectomized GD1 patient on long-term enzyme replacement therapy (ERT) who reported worsening fatigue and showed a progressive increase in Lyso-Gb1 levels after switching treatment from ERT to eliglustat. We provide a discussion of the potential clinical factors contributing to this outcome. As seen with ERT, Lyso-Gb1 levels during eliglustat treatment appear to respond earlier than other biochemical and clinical parameters. An increase in Lyso-Gb1 may signal early compromised clinical efficacy of the treatment. Data on biochemical and clinical outcomes in splenectomized or obese patients treated with eliglustat are limited, and the role of specific genotypes requires further clarification. The variability in responses to eliglustat highlights the complexity of GD and underscores the need for personalized approaches to treatment and monitoring.